Índice de qualidade da dieta e fatores associados em adultos de Cuiabá - Loureiro, Anarlete da Silva (2012)
Introduction: Changes in lifestyle are associated with increased health risk factors, especially those related to food. Dietary indexes summarize feeding characteristics that allow assessing possible deficiencies and / or excess of nutrients or food groups. Objective: To assess the quality of diet and to identify associated factors among adults living in the urban area of Cuiabá city, Mato Grosso State, Brazil. Methods: Crosssectional study with a sample drawn from population-based study with 195 adults aged 20 to 50 years, of both sexes. Dietary data were obtained through a food frequency questionnaire. Sociodemographic, lifestyle, anthropometric and body composition data were collected. Quality of diet was analyzed using the Diet Quality Index Revised (DQI-R), adapted for the Brazilian population. To compare the means, the MannWhitney test (p<0.05) was used, and associations were estimated by logistic regression. Results: DQI-R mean was 75.2 points (CI 95%: 74.2-76.1), with statistically significant difference between sexes (p=0.03). The score for each food group showed that men had higher scores for oils, oily food and fish fat (9.4 vs. 8.9; p=0.02) as compared with women. For the group of whole fruits and sodium, the score was higher for women, with respectively (4.7 vs. 4.2; p<0.01) and (2.9 vs. 1.9; p<0.01). Individuals aged ≥ 30 years had higher scores for both total DQI-R (76.4 vs. 73.6; p<0.01) and for the group of whole fruits (4.7 vs. 4.2; p<0.01), saturated fat (9.0 vs. 8.5; p<0.01) and calories from solid fat, alcohol and added sugar. Logistic regression between the adequate DQI-R and independent variables showed association for women, for individuals aged ≥ 30 years and for those whose household head had higher education. Conclusion: Women had better scores for whole fruits and sodium, while among men the scores for oils, oily food and fish fat were higher. Older individuals had higher scores for whole fruit, saturated fat and calories from solid fat, alcohol and added sugar. Men consumed more total vegetables; dark green and orange vegetables and legumes; meat, eggs and legumes; and oils, oily food and fish oil. Factors associated with adequate DQI-R were age, sex and education of household head.